(untitled) (Journal of Philosophy, Culture and Political Science, 2022)
Current global processes in the field of building new architecture of the world economic market draws attention to integration associations that are being created. Nowadays EAEU is one of the dynamically developing economic integration associations in Eurasian area. The Union is an international organization for regional economic integration with international legal capacity and competence. The worldwide geopolitical and economic crises affects on functioning and state of the integration projects. Hence, the purpose of the study is to analyze existing conditions of EAEU and factors, risks, prospects of Kazakhstan’s participation in EAEU under the conditions of modern political reality and instability. The authors conclude that according to analysis the greatest risk for Kazakhstan within EAEU structure is political risk. Political risk prevails over economic one and causes the greatest concerns. Moreover, authors give different prospects as to EAEU development.